Behavioral Telehealth Consultation with Families of Children with Autism Spectrum Disorder. (26th April 2016) - Machalicek, Wendy; Lequia, Jenna; Pinkelman, Sarah; Knowles, Christen; Raulston, Tracy; Davis, Tonya; Alresheed, Fahad
Abstract : In this study, desktop video teleconferencing was used to facilitate behavioral consultation at a distance with three parents of school‐age children with autism spectrum disorders. Parents were supported via desktop video teleconferencing as they conducted functional analyses and learned to implement an antecedent manipulation strategy, functional communication training, and a consequence‐based strategy. Parents then conducted a brief multi‐element treatment comparison to evaluate the preliminary effectiveness of each intervention strategy on their child's challenging behavior. The results of this study provide additional support to previous research suggesting that a telehealth model of behavioral consultation may be an effective way to assist parents of children with autism spectrum disorders address challenging behavior that disrupts family routines. Suggestions for future research are discussed. Copyright © 2016 John Wiley & Sons, Ltd.